Retirement preparedness and anticipation among Saudi female working professionals - Tahreem Noor Khan (Asian Journal of Management, Entrepreneurship and Social Science, 2022)
Planning for retirement requires a conscious decision on the individual to allocate or put aside income to allow for financial security upon retirement. The purpose of this research is to explore whether Saudi females have an optimistic perspective and preparedness about retirement. This research surveyed 315 Saudi female working professionals regarding anticipation for retirement to evaluate their attitude, knowledge, and future aspiration toward retirement. The result of this research has implications for working individuals to make early planning for retirement to enable them to have a strong base after retirement. Hence, they will be more confident and prepared to face the reality of life during retirement. The findings provide implications for modular (government, financial institutions, educators, and employers) who can contribute to the responsible retirement process.